2012
DOI: 10.1371/journal.pone.0050125
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Tumor Cell Death through Targeting Tubulin and Evoking Dysregulation of Cell Cycle Regulatory Proteins by Multifunctional Cinnamaldehydes

Abstract: Multifunctional trans-cinnamaldehyde (CA) and its analogs display anti-cancer properties, with 2-benzoyloxycinnamaldehyde (BCA) and 5-fluoro-2-hydroxycinnamaldehyde (FHCA) being identified as the ortho-substituted analogs that possess potent anti-tumor activities. In this study, BCA, FHCA and a novel analog 5-fluoro-2-benzoyloxycinnamaldehyde (FBCA), were demonstrated to decrease growth and colony formation of human colon-derived HCT 116 and mammary-derived MCF-7 carcinoma cells under non-adhesive conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 33 publications
(42 reference statements)
1
33
0
1
Order By: Relevance
“…In addition, we found that CA treatment suppresses tumor growth in mice and vessel formation in tumors. CA reduced HIF-1a and VEGF expression in cancer cells, and it has been reported to have antioxidant and anti-inflammatory actions [19][20][21][51][52][53]. These collective findings suggest that CA could be an effective cancer therapeutic agent through its orchestrated actions on apoptosis and angiogenesis in cancer and vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, we found that CA treatment suppresses tumor growth in mice and vessel formation in tumors. CA reduced HIF-1a and VEGF expression in cancer cells, and it has been reported to have antioxidant and anti-inflammatory actions [19][20][21][51][52][53]. These collective findings suggest that CA could be an effective cancer therapeutic agent through its orchestrated actions on apoptosis and angiogenesis in cancer and vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 76%
“…CAD is derived from the essential oil of cinnamon bark and is a highly bioactive compound serving many purposes (Jayaprakasha and Rao, 2011). It has been used as an anticancer agent (Nagle et al, 2012), an insecticide (Cheng et al, 2009), a fungicide (Bang et al, 2000;Shreaz et al, 2011), and a bactericide (Nostro et al, 2012). It is also used commercially as an additive in many foods and in fragrances (Cocchiara et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It is a "Generally Regarded As Safe" molecule according to the Food and Drug Administration (1). Previous studies have suggested TC has antitumor activities (23). However, its antisenescence properties have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%